Do immigrant workers depress the wages of native workers? - Giovanni Peri (IZA World of Labor, 2014)
Politicians, the media, and the public express concern that immigrants depress wages by competing with native workers, but 30 years of empirical research provide little supporting evidence to this claim. Most studies for industrialized countries have found no effect on wages, on average, and only modest effects on wage differentials between more and less educated immigrant and native workers. Native workers' wages have been insulated by differences in skills, adjustments in local demand and technology, production expansion, and specialization of native workers as immigration rises.
Keywords: J61; J31; F22; R23; 330; immigration; wages; productivity; complementarity; skills; wage distribution; dynamic adjustments